Development of a Web-Based Workshop Information System for Service Management and Customer Satisfaction Evaluation - Irfan Humaini; Aulian Abila (Lentera Ilmu Nusantara, 2026)
Junian Jaya Motor Workshop still manages service schedules, customer data, transactions, and operational reports manually, resulting in overlapping schedules, potential data loss, and difficulties in preparing daily and monthly reports. This study aims to develop a web-based workshop information system that supports service booking, scheduling, transaction recording, payment status monitoring, and customer satisfaction evaluation through a questionnaire feature. This study employed the Research and Development method using the System Development Life Cycle waterfall model, which consists of requirements analysis, system design, implementation, testing, evaluation, and maintenance. Data were collected through observation, interviews, and a literature review. The system was developed using PHP, HTML, CSS, JavaScript, and MySQL, with XAMPP as the local server. Functional testing was conducted using black-box testing with both valid and invalid input scenarios. The results showed that all 20 testing scenarios, consisting of 14 user-feature scenarios and six administrator-feature scenarios, produced the expected outputs and passed successfully. Features including registration, login, service booking, payment status checking, questionnaire submission, message delivery, input validation, and administrator data management functioned according to the specified requirements. Therefore, the developed system is functionally feasible to support more structured and efficient workshop service management while providing customer feedback for service evaluation.